Zerumbone induces apoptosis in human acute leukemia Jurkat T-cell line - Rahman, Heshu Sulaiman; Abdullah, Rasedee; Abdul, Ahmad Bustamam; Othman, Hemn Hassan; Allaudin, Zeenathul Nazariah; Wun, H. C.; Yeap, Swee Keong (2012)
Zerumbone (ZER) is a potential anticancer natural phytochemical compound, isolated from Zingiber zerumbet (L.) Smith. In this investigation, the anticancer properties of ZER were evaluated on cancer cells of T-acute lymphoblastic leukemia, Jurkat cells using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay and microscopic investigation (Flouresent microscope and scanning electron microscope). The results showed that ZER has cytotoxic effect against Jurkat cell in time dependent manner (24, 48 and 72h) with an IC50 of 11.875±0.178μg/ml, 8.593±0.480μg/ml and 5.397±0.431μg/ml respectively. Comparatively, doxorubicin (positive control) imposed an inhibitory effect on Jurkat cells with an IC50 of 1.514±0.070μg/ml after 72hr incubation. The results also revealed that ZER induced apoptosis time dependently in Jurkat cells using Annexin-v double staining assay. The current finding conducted that ZER with its unique chemical structure and versatile pharmacological activities might be helpful for improving the usefulness of anticancer agents in the therapy of leukemia.